2018
DOI: 10.2118/185095-pa
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Pressure and Wettability Indications of Middle Bakken Core Plugs for Improved Oil Recovery

Abstract: Summary Understanding reservoir-rock characteristics and the forces that mobilize oil in unconventional reservoirs is critical in designing oil-recovery schemes. Thus, we conducted laboratory experiments for three preserved Middle Bakken cores using centrifuge and nuclear-magnetic-resonance (NMR) instruments to understand oil-recovery mechanisms in the Bakken. Specifically, we measured capillary pressure, pore-size distribution (PSD), and oil and brine saturations and distributions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Another investigation with Bakken cores indicated that while the amount of oil recoverable with LSW was not large, it was significantly greater than that obtained with high salinity brine . During a study of capillary pressure and wettability, the same team demonstrated that when LSW was used, oil production from Middle Bakken cores via spontaneous imbibition was comparable to that achieved with forced imbibition, which indicated that molecular diffusion and capillary osmosis were more dominant than wettability effects regarding oil recovery …”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another investigation with Bakken cores indicated that while the amount of oil recoverable with LSW was not large, it was significantly greater than that obtained with high salinity brine . During a study of capillary pressure and wettability, the same team demonstrated that when LSW was used, oil production from Middle Bakken cores via spontaneous imbibition was comparable to that achieved with forced imbibition, which indicated that molecular diffusion and capillary osmosis were more dominant than wettability effects regarding oil recovery …”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 99%
“…271 During a study of capillary pressure and wettability, the same team demonstrated that when LSW was used, oil production from Middle Bakken cores via spontaneous imbibition was comparable to that achieved with forced imbibition, which indicated that molecular diffusion and capillary osmosis were more dominant than wettability effects regarding oil recovery. 272 5.2. Alkaline Solutions for EOR in ULRs.…”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 99%
“…Ternary plot of minerals for different basins (Ordos Basin, , Fort Worth Basin, , Maverick Basin, ,, Williston Basin, , Bohaiwan Basin, ,,,, Songliao Basin, − , Permian Basin, and Junggar Basin).…”
Section: Shale Mineralogy Pore Structure and Fluid Propertiesmentioning
confidence: 99%
“…The pore shape is a descriptive parameter and can be well-measured using observational methods, such as scanning electron microscopy (SEM), or modeled from lowpressure N 2 adsorption/desorption isotherm hysteresis curves. 81 Shale pore shapes are mainly slit, ink-bottle, honeycomb, bubble, elliptical, cylindrical, elongated, and 38,50,55 Williston Basin, 38,43 Bohaiwan Basin, 5,49,66,67,104 Songliao Basin, [57][58][59]71 Permian Basin, 55 and Junggar Basin 71−73 ).…”
Section: Shale Mineralogy Pore Structure and Fluid Propertiesmentioning
confidence: 99%
“…All of the arguments pointed out above should be taken into account in optimizing huff-n-puff field gas EOR implementation in unconventional reservoirs. The optimization is necessary in order to maximize the value of unconventional oil reserves through the increase in oil recovery. An approach that can be used in formulating the optimization strategy is through the determination of the most favorable conditions for oil production that can be achieved by the modification of the operational parameters, such as the amount of gas injected.…”
Section: Introductionmentioning
confidence: 99%